2014
DOI: 10.1126/scisignal.2005051
|View full text |Cite
|
Sign up to set email alerts
|

The ABA Receptor PYL8 Promotes Lateral Root Growth by Enhancing MYB77-Dependent Transcription of Auxin-Responsive Genes

Abstract: The phytohormone abscisic acid (ABA) regulates plant growth, development, and abiotic stress responses. ABA signaling is mediated by a group of receptors known as the PYR1/PYL/RCAR family, which includes the pyrabactin resistance 1–like protein PYL8. Under stress conditions, ABA signaling activates SnRK2 protein kinases to inhibit lateral root growth after emergence from the primary root. However, even in the case of persistent stress, lateral root growth eventually recovers from inhibition. We showed that PYL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
256
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(262 citation statements)
references
References 70 publications
6
256
0
Order By: Relevance
“…ABA-activated SnRK2s phosphorylate transcription factors, such as ABA-responsive element-binding factors (ABFs), and these phosphorylated ABFs regulate the expression of ABA-responsive genes (15). In Arabidopsis, 14 PYLs function diversely and redundantly in ABA and drought-stress signaling (16)(17)(18)(19). Understanding how each…”
mentioning
confidence: 99%
“…ABA-activated SnRK2s phosphorylate transcription factors, such as ABA-responsive element-binding factors (ABFs), and these phosphorylated ABFs regulate the expression of ABA-responsive genes (15). In Arabidopsis, 14 PYLs function diversely and redundantly in ABA and drought-stress signaling (16)(17)(18)(19). Understanding how each…”
mentioning
confidence: 99%
“…38 According to the literatures, it is proposed that the dimeric receptors act as the key targets for chemical modulation of vegetative ABA responses as well as the objective receptors for protein engineering, [5][6]39 while the monomeric ones prefer implicated in genetic-modify plant traits for abiotic stress tolerance 2 and also involved in root function regulation. [17][18]23 That the more sensitive of shoot growth than root growth in response to draft stress, is resulted from the insufficient ABA level in the former than the latter to restrict ethylene production. 11 It was shown that leaf ABA concentration ([ABA]) varied greatly as a result of plant growth under different levels of soil water deficit at moderate (60%) or high (90%) relative air humidity (RH).…”
Section: Spatio-temporal Specificities Of Pyr1/pyl/rcar Aba Receptorsmentioning
confidence: 99%
“…11 It is well known that osmotic stress-derived ABA can reduce leaf hydraulic conductivity and shoot growth, thus reducing the transpiration rate in Arabidopsis leaves, [12][13][14] whereas it can maintain root water uptake by enhancing root growth and root hydraulic conductivity. 8,11,[15][16][17] Recently it is found that the single PYL8 ABA receptor play a key role in mediating ABA-controlled root growth and root response to moisture gradient, means hydrotropism, [17][18] while there is a obvious redundant characteristics of PYR1/PYL/RCAR ABA receptor family in stomatal aperture regulation. 9 A naphthalene sulfonamide ABA agonist pyrabactin, which activates seed ABA responses but fails to trigger substantial responses in vegetative tissues in Arabidopsis thaliana.…”
mentioning
confidence: 99%
See 2 more Smart Citations